Applying CGC (Close Gank Challenge) Technique to Increase Students’ Speaking Skill: Dessy Kusumawati - Dessy Kusumawati (JPGENUS: Jurnal Pendidikan Generasi Nusantara, 2023)
CGC is an innovative method from the Conversation method but this one has different ways to teach English. CGG is focused on speaking that takes part everywhere in daily activities. This approach encourages students’ participation and gets ready the students to face real-life communication. At the leading edge, conversation manner can actually boost the students speaking and self-confidence. The type of research used in this study is classroom action research. The subject of this study is the students in 9th Grade of SMP IT AL-HILMI Dompu. The class chosen is 9th Akhwat Grade that consists of 20 students within. In conducting the research, the researcher did classroom observation, video recording, and an interview to make sure the students comprehension. , Research findings determined that the action and implication of the CGC technique in the teaching-learning process of speaking skill continued to improve. All of these data indicated that the students demonstrated a positive attitude and response during the teaching learning process CGC (Close-Gank Challenge) technique assisted students in learning how to speak easily. Based on the data and data analysis, it appeared that the student’s scores much improved